PENGARUH PENDIDIKAN KARAKTER DALAM PEMBELAJARAN AKUNTANSI KEUANGAN TERHADAP SIKAP ETIS MAHASISWA - Ghofirin, Mohammad (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
Character education is an education that is oriented not only to the mastery of teaching science (knowledge) but also the noble character (good character). The purposes of the study was to investigate the effect of character education which is integrated in financial accounting teaching and learning process to the students’ ethical attitudes. The results of the study showed that character education doesn’t affects students’ ethical attitudes (Sig 0.65 > 0.05). Therefore, it can be concluded from this study that character education integrated in financial accounting teaching and emotional intelligence affects the students’ ethical attitudes. The suggestions derived from the results of this study are: (1) For Accounting Department, State University of Malang, character education should be integrated explicitly on the whole subject of accounting department. (2) For lecturers, it is suggested to be willing and actively integrate character education in accounting teaching. (3) For other researchers, further research to examine the relationship between two independent variables is needed to be conducted. Therefore, it can be known whether one of the variables serve as a mediating or moderating variable.